2017
DOI: 10.3390/su9071271
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Infiltration and Evaporation of Diesel and Gasoline Droplets Spilled onto Concrete Pavement

Abstract: Pollution at gas stations due to small spills that occur during vehicle refueling have received little attention. We have performed laboratory experiments to assess evaporation and infiltration of fuel spilled onto concrete. Changes in the concrete mass after small amounts of diesel and gasoline were spilled have been analyzed. Variation in humidity, among other parameters, clearly affects the measured mass since condensed water is constantly added to or released from the concrete. This mass experiences an abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Sources of unburned fuel releases at gas stations include leaks from storage tanks, accidental spills from the nozzles of gas dispensers, [13][14][15] fugitive vapor emissions through leaky pipes and fittings, vehicle tank vapor releases when refueling, and leaky hoses, all of which can contribute to subsurface and air pollution. 2 Routine fuel releases also occur through vent pipes of fuel storage tanks but are less noticeable because the pipes are typically tall, e.g., 4 m. These vent pipes are put in place to equilibrate pressures in the tanks and can be located as close as a few meters from residential buildings in dense urban settings (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Sources of unburned fuel releases at gas stations include leaks from storage tanks, accidental spills from the nozzles of gas dispensers, [13][14][15] fugitive vapor emissions through leaky pipes and fittings, vehicle tank vapor releases when refueling, and leaky hoses, all of which can contribute to subsurface and air pollution. 2 Routine fuel releases also occur through vent pipes of fuel storage tanks but are less noticeable because the pipes are typically tall, e.g., 4 m. These vent pipes are put in place to equilibrate pressures in the tanks and can be located as close as a few meters from residential buildings in dense urban settings (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of fuel corrosion on the performance of asphalt and asphalt mixtures have been conducted mainly by comparing changes in the mechanical properties of asphalt mixtures before and after fuel corrosion. To evaluate the extent of the effect of diesel leakage on asphalt concrete pavements, their mass loss, adhesive properties, rutting resistance, and resistance to water damage have been evaluated [2][3][4][5][6][7][8][9]. For example, Chen [5] investigated the effect of gasoline and diesel corrosion on the high-temperature performance of asphalt mixtures using Marshall specimens and rutted plate specimens and found that the oil erosion process significantly reduces the Marshall stability and dynamic stability of asphalt mixture specimens.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang [6] found that the properties of asphalt and asphalt mixtures deteriorate significantly after oil corrosion. Moreover, diesel and gasoline affect asphalt and asphalt concrete to different extents [5][6][7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The fuel oil corrosion might cause pitting disease on asphalt pavement in a short time. In the meantime, the skid resistance, high temperature stability and water stability deteriorate dramatically, therefore threatening the road durability, driving comfort and safety [10][11][12][13][14][15][16]. Hence, it is of great significance to investigate and develop adaptable technology to improve the oil corrosion resistance of asphalt pavement.…”
Section: Introductionmentioning
confidence: 99%